2021
DOI: 10.1371/journal.pone.0248892
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy and resistance: Correlates in a nationally representative longitudinal survey of the Australian population

Abstract: Background High levels of vaccination coverage in populations will be required even with vaccines that have high levels of effectiveness to prevent and stop outbreaks of coronavirus. The World Health Organisation has suggested that governments take a proactive response to vaccine hesitancy ‘hotspots’ based on social and behavioural insights. Methods Representative longitudinal online survey of over 3000 adults from Australia that examines the demographic, attitudinal, political and social attitudes and COVID… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
248
6
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(327 citation statements)
references
References 16 publications
(20 reference statements)
43
248
6
8
Order By: Relevance
“…The most commonly cited reason for not getting vaccinated was concern about adverse reactions in more than 70% of the respondents. In addition, distrust toward the government and toward government policy on COVID-19 were observed to be factors related to the hesitancy, which is consistent with previous studies [ 23 , 24 , 25 ]. Other cited reasons for the hesitancy unique to the COVID-19 vaccine were the new mechanism of administration of mRNA by some vaccines, and the fast vaccination approval process [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…The most commonly cited reason for not getting vaccinated was concern about adverse reactions in more than 70% of the respondents. In addition, distrust toward the government and toward government policy on COVID-19 were observed to be factors related to the hesitancy, which is consistent with previous studies [ 23 , 24 , 25 ]. Other cited reasons for the hesitancy unique to the COVID-19 vaccine were the new mechanism of administration of mRNA by some vaccines, and the fast vaccination approval process [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, there have been studies [47] that cite negative relationship between vaccination and being married (or in a steady relationship). The result that males are on average less hesitant than females is consistent with the nding by [32] in the Australian context.…”
Section: Multivariate Analysissupporting
confidence: 85%
“…Exceptions are Chu and [31] in the US context and [28] in the context of China which used the EPPM and HBM frameworks respectively to assess COVID19 vaccine behaviour. [32] has identi ed the correlates of vaccine hesitancy in Australia, without the use of a speci c theoretical framework. The authors have not been able identify a study in the South African context on COVID19 vaccine intention.…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of comfort and confidence were associated to acceptance of a COVID‐19 vaccine (21). An Australian study reported that women, those with low perceived risk of COVID‐19, and those less trustworthy of vaccination programs were more likely to be resistant of vaccination (31). In our survey, women were less comfortable receiving a vaccine and more fearful of risks, consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%